Effect of liquid flow velocity on corrosion behavior of 20# steel at initial stage under gas-liquid two-phase plug flow condition. Issue 4 (17th April 2020) - Yang, Guirong; Song, Wenming; Zhu, Zibo; Ma, Ying; Hao, Yuan
Abstract : Purpose: The paper aims to study the effect of liquid flow velocity on corrosion behavior of 20# steel at initial stage under (CO2/aqueous solution) gas–liquid two-phase plug flow conditions. Design/methodology/approach: Weight loss, scanning electron microscopy, energy-dispersive X-ray spectroscopy and XPS methods were used in this study. Findings: The corrosion rate increased with the increasing liquid flow velocity at any different corrosion time. The corrosion rate decreased with the extension of corrosion time at the same liquid flow velocity. There was no continuous corrosion products film on the whole pipe wall at any different corrosion time. The macroscopic brown-yellow corrosion products on the pipe wall surface decreased with the increasing liquid flow velocity and the loose floccus corrosion products decreased gradually until these products were transformed into un-continuous needle-like dense products with the increasing liquid velocity. The main elements among the products film were Fe, C and O, and the main phases of products film on the pipe wall were Fe3C, FeCO3, FeOOH and Fe3O4. When the corrosion time was 1 h under different liquid–velocity condition, the thickness of local corrosion products film was from 3.5 to 3.8 µm. Originality/value: The ion mass transfer model of corrosion process in pipe was put forward under gas–liquid two-phase plug flow condition. The total thickness of diffusion sublayer and turbulence sublayer decreased as well as the turbulence propagation coefficient increased with the increasing liquid velocity, which led to the increasing velocity of ion transfer during corrosion process. This was the fundamental reason for the increase of corrosion rate with the increasing liquid velocity.